The summer cottage - Rains, Annie (Forever, 2021)
"Somerset Lake is the perfect place for Trisha Langly and her son to start over. As the new manager for the Somerset Cottages, Trisha is instantly charmed by the property's elderly residents and her firecracker of a new boss, Vi Fletcher. But Trisha is less enchanted by Vi's protective grandson Jake. No matter how tempting she finds the handsome lawyer, Trisha knows that if Jake discovers the truth about her past, she'll lose the new life she's worked so hard to build. Jake Fletcher left Somerset Lake after a tragic loss, but he's returning for the summer to care for his beloved grandmother, hoping Vi will sell the run-down cottages and finally slow down. There's just one problem: Trisha, Vi's new employee. She's smart, beautiful, and kind, but Jake's job is to protect his grandmother's interests, and his gut is telling him Trisha's hiding something that could jeopardize Vi's future. However, as they spend summer days renovating the property and bonding over their love for the town, Jake realizes that Trisha is a risk worth taking--if only she can trust him with her secrets . . . and her heart."--Amazon.